Enhancing work commitment among international employees - Kalliovaara, Taru (My University, 2026)
This study explores the factors influencing work commitment among international employees in the Finnish gaming industry. The research aims to identify what attracts highly skilled professionals to Finland stay in Finland, the challenges they face during integration, and the organizational practices that enhance their engagement and long-term retention. The study responds to a growing need for strategies that support global talent management in a competitive industry. The research is based on qualitative methods, specifically seven thematic interviews with international professionals working in Finnish gaming companies. The interviews examined employees’ perceptions of Finnish work culture, societal characteristics, social integration, and career development opportunities. Thematic analysis was used to identify key patterns and insights across participants’ experiences. Findings indicate that Finland’s stability, societal trust, and work-life balance are central factors supporting work satisfaction and commitment. At the same time, challenges related to social integration, language barriers, and perceived career limitations influence long-term retention. Organizational support, inclusive workplace practices, and opportunities for professional growth emerged as critical elements for enhancing engagement among international employees. Overall, the study highlights the interaction between professional and personal factors in shaping commitment. Recommendations for organizations include fostering social integration, supporting language acquisition, and ensuring transparent career pathways. These measures can improve the experiences of international employees and strengthen Finland’s attractiveness as a destination for skilled global talent.

Tämä tutkimus tarkastelee tekijöitä, jotka vaikuttavat kansainvälisten työntekijöiden sitoutumiseen suomalaisella pelialalla. Tutkimuksen tavoitteena on selvittää, mikä houkuttelee korkeasti koulutettuja ammattilaisia pysymään Suomessa, millaisia haasteita he kohtaavat integroitumisessa ja mitkä organisaatiokäytännöt edistävät sitoutumista ja pitkäaikaista pysymistä työpaikalla. Tutkimus vastaa kasvavaan tarpeeseen kehittää strategioita globaalin osaamisen hallinoimiseen kilpailuilla aloilla. Tutkimus perustuu kvalitatiivisiin menetelmiin, erityisesti seitsemään teemahaastatteluun kansainvälisten ammattilaisten kanssa, jotka työskentelevät suomalaisissa peliyrityksissä. Haastatteluissa tarkasteltiin työntekijöiden näkemyksiä suomalaisesta työkulttuurista, yhteiskunnallisista piirteistä, sosiaalisesta integroitumisesta ja urakehitysmahdollisuuksista. Temaattinen analyysi auttoi tunnistamaan keskeisiä kuvioita ja havaintoja osallistujien kokemuksista. Tutkimus osoittaa, että Suomen vakaus, yhteiskunnallinen luottamus ja työn ja vapaa-ajan tasapaino ovat keskeisiä tekijöitä, jotka tukevat työtyytyväisyyttä ja sitoutumista. Samanaikaisesti sosiaaliseen integroitumiseen, kielimuurin aiheuttamiin haasteisiin ja koettuihin urarajoitteisiin liittyvät tekijät vaikuttavat pitkäaikaiseen pysymiseen. Organisaation tuki, osallistavat työympäristökäytännöt ja mahdollisuudet ammatilliseen kasvuun nousevat keskeisiksi tekijöiksi kansainvälisten työntekijöiden sitoutumisen vahvistamisessa. Tutkimus korostaa ammatillisten ja henkilökohtaisten tekijöiden yhteisvaikutusta sitoutumisen muodostumisessa. Organisaatioille suositellaan sosiaalisen integroitumisen tukemista, kielen oppimisen edistämistä ja läpinäkyvien urapolkujen varmistamista. Näillä keinoilla voidaan parantaa kansainvälisten työntekijöiden kokemuksia ja vahvistaa Suomen houkuttelevuutta osaajien kansainvälisenä kohteena.
Keywords: international employees, work commitment, global talent, employee retention, Finnish gaming industry, work-life balance, social integration, career development, kansainväliset työntekijät, sitoutuminen, globaalit osaajat, työntekijöiden pysyvyys, suomalainen peliala, työn ja vapaa-ajan tasapaino, sosiaalinen integraatio, urakehitys